Optimalisasi Keuntungan Usaha melalui Pelatihan Pembudidayaan Varietas Cabai Unggul yang Tahan Organisme Pengganggu Tanaman dan Pengelolaan Pasca Panen: Optimizing Business Profits through Cultivation of Superior Chilli Varieties Resistant to Crop Pests and Post-Harvest Management - Jovan Febriantoko; Tri Tunggal; Rian Rahmanda Putra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Growing vegetables is a support to the family economy for farmers. The living conditions of fellow farmers are still far from good. The purpose of the Community Science and Technology Application in empowering Independent Advanced Farmer Groups is to provide solutions to problems in the aspects of production, management, marketing, management and post-harvest management. Thus, it has an impact in increasing the empowerment of partners. The methodology used in the application of community science and technology is training and direct practice in the field. Pre-Community Service and post Community Service results, Farmers in this activity experience increased knowledge up to 90.34%. The highest increase in knowledge results lies in the knowledge achievement indicator related to Understanding Superior Variety Seeds, while the lowest percentage increase is in the knowledge achievement indicator Understanding Post-Harvest Processing, which is 78.67%. The average level of improvement in the achievement of knowledge indicators is 45.23% of the knowledge previously possessed. The conclusion of this community service is the improvement of partners from various aspects such as the understanding of seeds of superior varieties, knowledge of planting techniques, the ability to install agricultural tools, understanding of post-harvest processing, knowledge of digital promotion and the ability to prepare financial reports.